2004
DOI: 10.1007/s00787-004-1011-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an adaptive multimodal treatment in children with Attention?Deficit Hyperactivity Disorder ? global outcome

Abstract: Both, behaviour therapy and combined treatment are effective interventions within an adaptive and individually tailored multimodal treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
9

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 15 publications
0
56
0
9
Order By: Relevance
“…In certain conditions (such as oppositional-defiant/aggressive symptoms, internalizing symptoms, teacher rated social skills, parent-child relations, and reading achievement), combined treatment was superior to behavioral treatment and/or community care (21). On the contrary, other studies have demonstrated incremental results for adding behavior therapy to psychostimulant medication in terms of reductions of ADHD symptoms (32,33). Similarly, psychosocial interventions such as ICPS have been found to be effective for children with ADHD (34).…”
Section: Discussionmentioning
confidence: 99%
“…In certain conditions (such as oppositional-defiant/aggressive symptoms, internalizing symptoms, teacher rated social skills, parent-child relations, and reading achievement), combined treatment was superior to behavioral treatment and/or community care (21). On the contrary, other studies have demonstrated incremental results for adding behavior therapy to psychostimulant medication in terms of reductions of ADHD symptoms (32,33). Similarly, psychosocial interventions such as ICPS have been found to be effective for children with ADHD (34).…”
Section: Discussionmentioning
confidence: 99%
“…Danach konnten im Rahmen einer Studie zur adaptiven multimodalen Therapie von Kindern mit ADHS im Verlauf der verhaltenstherapeutischen Interventionen nach dem Therapieprogramm THOP Verhaltensauffälligkeiten in der Familie und in der Schule deutlich reduziert werden [6]. Weitere Studien, in denen das Elterntraining von THOP im Gruppen-oder im Einzelformat durchgeführt wurde, zeigten ebenfalls deutliche Effekte [10].…”
Section: > Elterntraining Und Interventionen In Kindergarten Und Schuunclassified
“…Allerdings erwies sich in der MTA-Studie die kombinierte Behandlung der unimodalen Pharmakotherapie auf einem Gesamterfolgsmaß als signifikant überlegen [3]. Auch die Kölner KAMT-Studie zeigte, dass ein adaptives Vorgehen besonders günstig ist, bei dem zunächst mit Pharmako-oder Verhaltenstherapie begonnen wird und dann in Abhängigkeit von den erzielten Effekten eine Kombination nur dann erfolgt, wenn sich die Symptomatik noch nicht hinreichend vermindert hat [6]. Darüber hinaus wiesen die Ergebnisse zu den Langzeiteffekten in diesen Studien darauf hin, dass bei psychosozialen Interventionen ähnliche Effekte erzielt werden können wie bei Pharmakotherapie [12,13,16].…”
Section: Introductionunclassified
“…Wie weit derartigen Empfehlungen in der Praxis gefolgt wird, ist allerdings kaum untersucht. Sorensen (1998) Döpfner et al (2004). Die Datenlage hat sich seitdem nur wenig verändert, beispielsweise durch die negativen Ergebnisse von Fluoextin bei Anorexia nervosa (Walsh, 2006).…”
Section: Schlagwörterunclassified